Droplet Microfluidics: High‐Throughput Optimization of Recombinant Protein Production in Microfluidic Gel Beads (Small 2/2021). Issue 2 (14th January 2021) - Napiorkowska, Marta; Pestalozzi, Luzius; Panke, Sven; Held, Martin; Schmitt, Steven
Abstract : In article number 2005523, Steven Schmitt and co‐workers present microfluidic optimization of biotechnological protein production. The artwork displays a series of gel beads, each containing a colony of Komagataella phaffii secreting a protein that is captured and fluorescently labeled within the beads. Laser‐based analysis identifies high‐producing clones.